2022
DOI: 10.1111/jocn.16516
|View full text |Cite
|
Sign up to set email alerts
|

Medical Device‐Related Pressure injuries in adult intensive care units

Abstract: Aim and Objective: This study was conducted to examine the development, characteristics, and risk factors of medical device-related pressure injury (MDRPI) in intensive care units (ICU). Background:The number of individuals admitted to ICU increased in the last years all over the world. In parallel with this need, the frequency of the use of life-support and therapeutic medical devices in the ICU also increases. This situation may lead to the development of MDRPI in the ICU and an increase in its prevalence. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…34,35 For both treatment groups, PIs developed most frequently due to antiembolic socks. Whereas some studies found that MDRPIs developed most frequently in ICU patients using endotracheal tubes, noninvasive mechanical ventilation masks, and oxygen masks, 33,[35][36][37] other research supports the present findings. 34,38,39 The authors hypothesize that nurses may prioritize the prevention of PIs related to other medical devices, leading to the high incidence of antiembolic socks-related PIs.…”
Section: Discussionsupporting
confidence: 80%
“…34,35 For both treatment groups, PIs developed most frequently due to antiembolic socks. Whereas some studies found that MDRPIs developed most frequently in ICU patients using endotracheal tubes, noninvasive mechanical ventilation masks, and oxygen masks, 33,[35][36][37] other research supports the present findings. 34,38,39 The authors hypothesize that nurses may prioritize the prevention of PIs related to other medical devices, leading to the high incidence of antiembolic socks-related PIs.…”
Section: Discussionsupporting
confidence: 80%
“…A prospective cohort study by Koo et al 28 found that 19.8% of 253 adult patients treated in ICUs developed MDRPIs. 27,28 Similarly, Barakat-Johnson et al 29 observed that approximately one-third of patients included in their study developed MDRPIs, with more than half of those patients being treated in ICUs. 29 The high frequency of occurrence noted in the present study is concerning, and demonstrates the importance of promptly reviewing measures to prevent MDRPI development.…”
Section: Discussionmentioning
confidence: 87%
“…According to the literature, MDRPIs develop in between 3.1% and 40% of intensive care patients. 13,14,19,22,27,28 In an observational and prospective descriptive study, Celik et al 27 found that approximately one-third of patients treated in ICUs developed MDRPI within a year. A prospective cohort study by Koo et al 28 found that 19.8% of 253 adult patients treated in ICUs developed MDRPIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape of the injury is often consistent with the shape of the medical devices. The prevalence of MDRPI in critically ill patients in the intensive care unit (ICU) is due to the frequent use of various medical devices, extensive drug therapy and patients' own characteristics such as skin edema 7‐10 . It is now one of the more serious adverse events in ICU patients 11,12 .…”
Section: Introductionmentioning
confidence: 99%